Islamic Environmental Ethics and Waste-to-Energy Innovation: Insights from the Quran - Derysmono, Derysmono; Al-Kahfi (UIN Syarif Hidayatullah Jakarta, 2025)
Angelika Neuwirth's intertextuality opens new insights into the Qur'an's relationship with the Environmental sustainability is a fundamental concern in modern society, and Islam provides ethical guidelines for responsible environmental stewardship. This study explores the principles of Islamic environmental ethics derived from the Quran and their relevance to waste-to-energy (WTE) innovation as a sustainable waste management strategy. The Quran emphasizes khalifah (stewardship), mizan (balance), and israf (avoidance of wastefulness) as key ethical foundations for environmental conservation. From an Islamic perspective, the transformation of waste into energy aligns with the maqasid shariah (higher objectives of Islamic law) by promoting environmental protection a nd public welfare. This research also examines existing WTE initiatives in Muslim-majority countries, highlighting challenges and opportunities in integrating Islamic values into technological advancements. The findings suggest that Islamic teachings can serve as a moral and spiritual foundation for promoting WTE solutions, encouraging policymakers, religious scholars, and communities to adopt environmentally responsible practices. This study contributes to the discourse on Islamic environmental ethics and provides policy recommendations for sustainable waste management in Muslim societies.